2021
DOI: 10.21037/atm-21-6427
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Aβ induces osteoporosis through an mTOR-dependent inhibition of autophagy in bone marrow mesenchymal stem cells (BMSCs)

Abstract: Background: It has previously been suggested that Alzheimer's disease (AD) and osteoporosis (OP) were related. However, the connection between these 2 disorders is poorly understood. This study aimed to investigate the relationship between amyloid β peptide (Aβ) and the osteoporotic deficit observed in AD patients.Methods: We used the APP/PS1ΔE9 transgenic mouse model of AD for in vivo study and extracted bone marrow mesenchymal stem cells (BMSCs) for in vitro studies. For in vivo experiments, mice femurs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Two pathways were found to be contributing to skeletal fragility in AD via alteration of bone quality: accumulation of AGEs and lack of crystallinity, reduced crystal size, and lack of mineralization ( 28 ). Another animal study showed that endogenous Aβ might induce osteoporosis via mTOR-dependent inhibition of autophagy in bone marrow mesenchymal stem cells (BMSCs) ( 29 ). Therefore, APP/Aβ has direct effects on bone cells and may play a vital function in the pathogenesis of bone fractures in AD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Two pathways were found to be contributing to skeletal fragility in AD via alteration of bone quality: accumulation of AGEs and lack of crystallinity, reduced crystal size, and lack of mineralization ( 28 ). Another animal study showed that endogenous Aβ might induce osteoporosis via mTOR-dependent inhibition of autophagy in bone marrow mesenchymal stem cells (BMSCs) ( 29 ). Therefore, APP/Aβ has direct effects on bone cells and may play a vital function in the pathogenesis of bone fractures in AD patients.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that activation/inhibition of mTOR signaling positively/negatively regulates BMSC/osteoblast-mediated bone formation, adipogenic differentiation, osteoblast homeostasis, and osteoclast mediated bone resorption, leading to altered bone homeostasis, which can lead to or prevent osteoporosis (Shen et al, 2018). Other studies have shown that amyloid β induces osteoporotic defects in vivo and in vitro through mTOR and autophagy, and the regulation of amyloid β on BMSCs is dependent on mTOR, thus providing a possible mechanism for osteoporotic remodeling in AD patients (Yang et al, 2019;Lin et al, 2021).…”
Section: Osteoporosismentioning
confidence: 99%
“…26 It is also reported that bone marrow mesenchymal stem cells (BMSCs) producing endogenous Aβ, which led to the activation of mammalian target of rapamycin (mTOR) and consequent inhibition of autophagy, impede the bone formation. 27 Additionally, supplementation of the inducing medium with mTOR inhibitor rapamycin reversed the inhibition of osteogenesis in vivo. 27 In vertebral trabecular bone specimens from a 45 female patient group with fresh vertebral compression fractures, osteoporotic bone tissues showed higher levels of Aβ peptide, which enhances osteoclast function.…”
Section: ■ Introductionmentioning
confidence: 99%
“…27 Additionally, supplementation of the inducing medium with mTOR inhibitor rapamycin reversed the inhibition of osteogenesis in vivo. 27 In vertebral trabecular bone specimens from a 45 female patient group with fresh vertebral compression fractures, osteoporotic bone tissues showed higher levels of Aβ peptide, which enhances osteoclast function. 25 In this study, we used the RANKL-induced osteoclast pretreated with Aβ model in vitro to examine the inhibitory effect of CTP on osteoclast differentiation, function, and related genes and proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation